Štajerske deželne službe pred letom 1311 - Bele, Martin (Studia Historica Slovenica, 2018)
The subject of the presented article are the regional ofces (regional captain/governor, regional judge, regional scribe), which diferent individuals in Styria held prior to the year 1311. Most of the holders of the considered offces were of noble pedigree, even though some were citizens of cities or even smaller market towns. Rare individuals held more than one office title at the same time or sometimes the same ofce during intermittent time periods. It was all a result of the current political situation. The main objective of the research was to create a list of all the regional office holders and secondly to present these individuals considering their geographical origin. The ones originating from today's Slovenian Styria, we also tried to highlight. Otherwise it must me pointed out that the sources useful to research the considered offices and their holders are scarce as well as unevenly preserved. Therefore the end result of information from them varies greatly.
Keywords: 12.-14.st.; javna uprava; regionalna uprava; Slovenija; Štajerska; zgodovina